Total Suspended Solid (TSS) Study in Gajah Mungkur Reservoir Based on Landsat Image Analysis - Astuti, Nurul; Murti, Sigit Heru; Widayani, Prima (Lambung Mangkurat University Press, 2024)
Total Suspended Solid (TSS), as one of the physical parameters of water quality, can also become an indicator in more comprehensive research themes. TSS is closely related to the process of erosion and sedimentation. One of the reservoirs that is experiencing serious problems with sedimentation is WGM. In terms of physical changes, alterations in water quality involve the introduction of both organic and inorganic solid particles, leading to elevated water turbidity and diminished penetration of sunlight into the water body. Remote sensing techniques can indirectly estimate and map TSS in bodies of water. Landsat imagery has been widely used in TSS studies. Not only is it able to identify water turbidity, but it also has a long time series and convenient data accessibility. The purpose of this research is to examine the TSS equation in the form of Normalised Suspended Material Index (NSMI) and the Syarif Budhiman Algorithm to obtain a comparison of results that are suitable for application to the waters of WGM using Landsat imagery. The results showed that the Syarif Budhiman Algorithm is considered more suitable to be applied to the study site based on statistical analysis using Landsat image data and field TSS sample data. The accuracy test results for the two equations did not show significant differences. The Syarif Budhiman equation showed a value of 37.87, and the NSMI equation of 37.47. However, the coefficient of model determination was 0.251 for NSMI and 0.340 for Syarif Budhiman. The distribution of TSS at the study site is generally homogeneously distributed with small concentrations ranging from 0-20 mg/L in the middle side of the reservoir. While the TSS class > 100 mg/L is scattered on the edge of the reservoir in Pondok, Keduang, Kepuh Wiroko, Temon, Bengawan Solo Hulu, Alang, and Kedungguling sub-watersheds